Potret UMKM Desa Pantai Labu: Analisis Tantangan, Strategi, Dan Kontribusi Ekonomi Lokal - syafii murad daulay (Smart GOALS Jurnal Bisnis Digital Dan Manajemen, 2025)
This study aims to analyze the challenges, strategies, and contributions of micro, small, and medium enterprises (MSMEs) to the local economy in Pantai Labu Village, Deli Serdang Regency. The research was conducted through direct interviews with MSME actors from various sectors, including fisheries, agriculture, livestock, and trade. The findings reveal that each MSME sector faces unique challenges, such as fluctuating raw material prices, adverse weather conditions, and market competition. Nevertheless, they employ creative strategies such as product diversification, mobile sales, and quality improvement to remain competitive. Additionally, MSMEs significantly contribute to the local economy by providing employment opportunities and stimulating regional economic activity. These insights are expected to inform policymakers in fostering the sustainability of MSMEs at the local level.